A WRITING SKILL ASSESSMENT OF THE FIRST SEMESTER ENGLISH DEPARTMENT STUDENTS OF THE UNIVERSITAS SUMATERA UTARA - Tania Tita Shanorra; Rudy Sofyan; Desri Maria Sumbayak (BAHAS, 2021)
Abstract  This study attempts to measure the students’ abilities in writing through online language learning platform using library research. The subject of the research was TOEFL top score in English Department USU consisting of 19 students. The instruments of collecting data were the students’ writing e-portfolio as the quantitative and qualitative data. Based on the assessment process, the used of online learning platform was very helpful, effective, and efficient both for the teachers and the students. The findings of the research: (1) Content aspect score was 25.7; (2) Organization aspect score was 18.1; (3) Vocabulary aspect score was 18.3; (4) Language use aspect score was 19.7; (5) Mechanics aspect score was 4.3. The result of the research showed that the students experienced mostly in excellent to very good level.Keywords: Assessment, Writing, Ability, Language, Learning